The Implementation of the Peer Teaching Learning Model Using the Demonstration Method to Improve Advanced Turning Skills - Aprilian, Johan Andric; Sumbodo, Wirawan; Sutopo, Yeri (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of the peer teaching model combined with the demonstration method on improving students’ skills in stepped turning (membubut bertingkat). The research was conducted on two groups: an experimental class using the peer teaching and demonstration approach, and a control class using conventional teaching methods. The research employed a quasi-experimental method with a pretest-posttest control group design. Data collection techniques included practical skill tests and documentation of student work. Data analysis was carried out using N-Gain scores and independent sample t-tests. The results showed that the experimental class achieved an average N-Gain of 79.02%, with most students falling into the “effective” category, while the control class reached an average of only 62.56%. The homogeneity test confirmed that the data variance was homogeneous. The t-test revealed a significance value of 0.000 < 0.05, indicating a statistically significant difference between the experimental and control groups. Thus, it can be concluded that the application of the peer teaching model with the demonstration method is significantly more effective in enhancing stepped turning skills than conventional teaching methods. This study recommends the implementation of collaborative and hands-on learning strategies in vocational technical education to improve practical competencies.